Gut microbiota and colorectal cancer: mechanistic insights, diagnostic advances, and microbiome-based therapeutic strategies - Bai, Bingbing; Ma, Jianing; Xu, Wenlong; Chen, Xiaomin; Chen, Xu; Lv, Chao; Su, Wei; Li, Yaoxu; Sun, Hongyin; Zhang, Baoyin; Xiang, Dejuan; Li, Zhongsha; et al. (Frontiers in Microbiology, 2025)
Colorectal cancer (CRC) is closely linked to gut microbiota dysbiosis. We synthesize evidence that carcinogenic microbes promote CRC through chronic inflammation, bacterial genotoxins, and metabolic imbalance, highlighting key pathways involving Fusobacterium nucleatum, pks+Escherichia coli, and enterotoxigenic Bacteroides fragilis (ETBF). Building on these mechanisms, we propose a minimal diagnostic signature that integrates multi-omics with targeted qPCR, and a pathway–therapy–microbiome matching framework to guide individualized treatment. Probiotics, fecal microbiota transplantation (FMT), and bacteriophage therapy show promise as adjunctive strategies; however, standardization, safety monitoring, and regulatory readiness remain central hurdles. We advocate a three-step path to clinical implementation—stratified diagnosis, therapy matching, and longitudinal monitoring—supported by spatial multi-omics and AI-driven analytics. This approach aims to operationalize microbiome biology into deployable tools for risk stratification, treatment selection, and surveillance, advancing toward microbiome-informed precision oncology in CRC.